Factors determining the style of adaptation to the disease in patients treated oncologically - Smoleń, Ewa; Słysz, Magdalena; Jarema, Magdalena; Hombek, Karolina; Kalita, Krzysztof (Journal of Education, Health and Sport, 2017)
Introduction. Cancer diseases still have the strongest impact on the human psyche, leading to the overwhelming life crisis. Each person, depending on personality traits and well-developed defense mechanisms, reacts individually to the diagnosis of the disease. Attitude towards the disease affects the quality of life and the outcome of treatment. Aim. Determination of factors determining the style of adaptation to cancer in patients during oncological treatment. Materials and methods. The research was conducted in a group of 229 randomly selected patients in Fr.. B. Markiewicz Specialist Hospital of the Podkarpacki Oncological Center. in Brzozów. The method used was a diagnostic survey and a survey technique. Research tools were the author’s questionnaire, „The scale of mental adaptation to cancer” - Mini-MAC (Mental Adjustment to Cancer) in the adaptation of Z. Juczyński and the numerical scale of pain assessment NRS (Numeric Rating Scale). In the statistical analysis, the following tests were used: Kruskal Wallis and the symmetric measure V Kramer based on the chi-square test. The statistical significance level p≤0.05 was assumed. Results. The level of adaptation to the disease in the studied group of oncological patients was on an average level, which indicates good adaptation to cancer. The dominant style of struggling with cancer was the construction style with the intensity of a fighting spirit and positive re-evaluation. The destructive style had a low intensity in the studied group, especially for a low level strategy of helplessness / hopelessness. Better adaptation has been demonstrated in individuals who do not experience pain and assess their health well. Conclusions. Factors not related to the style of coping with cancer were sociodemographic variables. Feeling of pain, self-esteem of health and applied methods of treatment influenced the style of coping with cancer in oncologically treated patients. The constructive style prevailing in the studied group in the struggle with cancer may positively affect the prognosis, duration of the survival, lack of remission of the disease and a better quality of life of patients treated oncologically.